A star for Mrs. Blake : a novel - Smith, April, 1949- (Alfred A. Knopf, 2014)
"An emotionally-charged, brilliantly realized novel set in the 1930's about five American women--Gold Star Mothers--who travel to France to visit the graves of their WWI soldier sons: a pilgrimage that will change their lives in unforeseeable and indelible ways. The women meet for the first time just before their journey begins: Katie, an Irish maid from Dorchester, Massachusetts; Minnie, wife of an immigrant Russian Jewish chicken farmer; Bobbie, a wealthy Boston socialite ; Wilhelmina, a former tennis star in precarious mental health; and Cora Blake, a single mother and librarian from coastal Maine. In Paris, Cora meets a journalist whose drug habit helps him hide from his own war-time fate--facial wounds so grievous he's forced to wear a metal mask. This man will change Cora's life in wholly unexpected ways. And when the women finally travel to Verdun to visit the battlegrounds where their sons fought as well as the cemeteries where they are buried, shocking events -a death, a scandal, a secret revealed--will guarantee that Cora's life and those of her traveling companions will become inextricably intertwined, and only now will they be able to emerge from their grief and return home to their loved ones. This is a timeless story set against a footnote of history: little known but unforgettable.."--